Efektivitas Kebijakan Pajak PPH Pasal 23 Terhadap Usaha Umkm - Ade Nurul Kaidah Sinaga; Elpi Yanti (Jurnal Ekonomi, Akuntansi, dan Perpajakan, 2025)
As a major contributor to GDP and job creation, Micro, Small, and Medium Enterprises (MSMEs) play an important role in the Indonesian economy. The purpose of this study is to evaluate the extent to which MSME business actors are able to support tax compliance while maintaining their business continuity through the implementation of the Income Tax (PPh) Article 23 policy. in the form of services, rent, profits, interest, and royalties are subject to PPh Article 23 tax. The implementation of the Income Tax Article 23 policy using taxation theory, public policy theory, tax law theory, and public management theory, this study uses a descriptive analysis methodology. The impact of the implementation of this tax on the financial and administrative aspects of MSMEs is examined, as well as the efficiency of the tax deduction system in increasing tax compliance. The results of the study, the application of a final rate of 0.5% based on PP No. 23 of 2018 and the supporting deduction / collection method in the PPh Article 23 policy, help ease the tax burden for MSMEs. The source deduction scheme has succeeded in increasing state revenues and ensuring tax compliance. There are still issues regarding the effectiveness of this policy, especially related to administrative compliance, such as processing certification, which is required to obtain a lower final rate. The main obstacles are literacy among MSMEs, lack of knowledge about the tax administration process, and the possibility of double taxation for MSMEs that do not have certificates are the main challenges noted. have not utilized the available incentives optimally due to lack of awareness and familiarity with the policy. This study concludes that in order to increase the effectiveness of the Income Tax Article 23 policy for MSMEs, significant efforts need to be made, such as tax education, simplification of administration, and strengthening supervision. The suggestion that can be given is that this policy can provide the greatest benefits for the growth and sustainability of MSME businesses which are the foundation of the national economy.